Share! Like! Create! How Fan Labor Is Cultivated And Practiced In The Contemporary Music Industry - Ryan Bengtsson, Linda; Fast, Karin; Ferrer Cornill, Raul (AoIR Selected Papers of Internet Research, 2017)
This paper explores how music consumers perform and act within transmedia marketing, focusing on music marketing campaigns. We follow the music consumers’ movement within the promotional campaign of one internationally known artist, capturing the their actions and interactions. Through an exploratory case study adopting a multi-method approach rooted in digital methods, we map how the consumers move through the campaign, how the campaign guides them through various media platforms, how consumers are engaged in the production of content and how this content then recirculates within the campaign. We argue that transmedia entertainment carries spatial qualities, and that the use of spatial metaphors offer both a way to explore the movement of the consumer as well as to represent and to visualize how the marketing campaign constructs immersive worlds where consumers transform into free labor – suggesting that we can understand transmedia campaigns as transmediascapes. Using spatial metaphors also provides us with a methodological approach to transmedia marketing, positioning actions and actors in relation to each other in time and space. Our preliminary results indicate that consumers within the music industry are mobilized as they assemble consumer affect and promote physical as well as virtual fan movement. The consumer follows a path constructed by the marketing campaign, making the consumer migrate between various spaces located in different platforms. Our paper also contributes with methodological development, where acknowledging the spatial dimensions of free labor and transmedia marketing provides a methodological approach to media consumers within contemporary transmediascapes.